The Impact of CAGE Institutional Distances and Motivations for Internationalization on the Brazilian Foreign Direct InvestmentbOutflows - Manuel Portugal Ferreira (FUCAPE Business School, 2019)
In this study, we have analyzed the influence of institutional distances and strategic motivations for internationalization on Brazilian foreign direct investment (FDI). We suggest that institutional differences, between Brazil and the host country, measured with Ghemawhat's (2001) CAGE typology, have a negative impact on FDI flows. However, we propose that the market-seeking and strategic asset-seeking motivations (e.g., new knowledge acquisition) moderate the impact of institutional differences on investment decisions by reducing the impact of the institutional distances between countries on investment decisions.